The role of radiotherapy-related autophagy genes in the prognosis and immune infiltration in lung adenocarcinoma - Gao, Jingyan; Lu, Fei; Yan, Jiawen; Wang, Run; Xia, Yaoxiong; Wang, Li; Li, Lan; Chang, Li; Li, Wenhui (Frontiers in Immunology, 2022)
Background: The prognostic value of radiotherapy-related autophagy genes (RRAGs) in LUAD remains unclear. Methods: Data used in the current study were downloaded from TCGA and GEO database. WGCNA was performed to identify module genes associated with radiotherapy. The differentially expressed genes (DEGs) between different radiotherapy response groups were screened by edgeR package. The differentially expressed radiotherapy-related autophagy genes (DERRAGs) were obtained by overlapping the module genes, DEGs, and autophagy genes (ATGs). Subsequently, prognostic autophagy genes were selected by univariate and multivariate regression analyses, followed by the construction of the risk score model and nomogram. GSEA and ssGSEA were performed to investigate the potential mechanisms of prognostic autophagy signature in regulating LUAD. The radiotherapy-resistant cell lines (A549IR and PC9IR) were established after exposure to hypo-fractionated irradiation. Ultimately, the mRNA expression levels were validated by quantitative real-time PCR (qRT-PCR). The relative protein levels in different cell lines were measured by western blot. Results: A total of 11 DERRAGs were identified in LUAD. After univariate and multivariate Cox regression analyses, SHC1, NAPSA and AURKA were identified as prognostic signature in LUAD. The risk score model was then constructed based on prognostic signature, which had a good performance in predicting the prognosis of LUAD, as evidenced by ROC curves in both training and validation sets. Furthermore, univariate and multivariate Cox regressions demonstrated that the risk score was an independent prognostic factor in LUAD. Moreover, GSEA and ssGSEA results revealed that prognostic RRAGs may regulate LUAD via modulating the immune microenvironment and affecting cell proliferation. Colony formation assay verifies that the radiosensitivity of radiation-resistant cell lines is lower than that of primary cells. The west blotting assay found the levels of autophagy were elevated in radiotherapy-resistant cell lines. The expression of DERRAGs (SHC1, AURKA) was higher in radioresistant cells than in primary cells. Conclusion: Our study explored the role of RRAGs in the prognosis of LUAD and identified three biomarkers for predicting the prognosis of LUAD patients. Our findings enhanced the understanding of the relationship between radiotherapy, autophagy and prognosis in LUAD, and provided potential therapeutic targets for LUAD patients.